A value-sensitive framework for informed consent: considerations from the WHO's Guidance for Human Genome Data Collection, Access, Use and Sharing (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The growing complexity of clinical genomic research challenges existing informed consent models, demanding frameworks that reflect the collective, dynamic, and relational nature of genetic data. Drawing on six ethical principles from the recent WHO’s Guidance for Human Genome Data Collection, Access, Use and Sharing — social justice, inclusivity, solidarity, responsible stewardship, transparency, and accountability — this paper proposes Value Sensitive Design as a methodological approach to translate normative aims into practice. It complements models like dynamic consent by integrating stakeholder values from the outset and enhancing ethical robustness, cultural sensitivity, and adaptability across diverse sociotechnical contexts. It also opens pathways for developing digital tools and speculative strategies for inclusive and forward-looking genomic data governance.
Keywords: genomics; informed consent; data governance; World Health Organization; Value Sensitive Design.